2015
DOI: 10.1002/smll.201501573
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable DNA‐Brush Block Copolymer Spherical Nucleic Acids Enable Transfection Agent‐Free Intracellular Gene Regulation

Abstract: A new strategy for synthesizing spherical nucleic acid (SNA) nanostructures from biodegradable DNA block copolymers is reported. Multiple DNA strands are grafted to one end of a polyester chain (poly-caprolactone) to generate an amphiphilic DNA brush block copolymer (DBBC) structure capable of assembling into spherical micelles in aqueous solution. These novel DBBC-based micelle-SNAs exhibit a higher surface density of nucleic acids compared to micelle structures assembled from an analogous linear DNA block co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 44 publications
(77 reference statements)
2
71
0
Order By: Relevance
“…By using various molar ratios, thiolated ssDNA and thiolated oligoethylene glycol strands to functionalize 13 nm gold (Au) cores to form SNAs of similar sizes, Giljohann et al previously observed a positive correlation between DNA loading density and intracellular delivery of Au‐cored SNAs to three cell types, including C166 endothelial cells, HeLa cells, and A549 lung cancer cells . Zhang et al arrived at a similar conclusion by preparing two sets of polymer‐cored SNAs with sizes of ≈40 nm, 1) micellar‐SNAs coated with DNA‐brush block copolymer (DBBC) strands (302 DNA strands per particle) and 2) micellar‐SNAs coated with linear block copolymer (LDBC) strands (190 DNA strands per particle) . The authors observed that DBCC–SNAs enter HeLa cells twice as much as LDBC–SNAs.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 91%
“…By using various molar ratios, thiolated ssDNA and thiolated oligoethylene glycol strands to functionalize 13 nm gold (Au) cores to form SNAs of similar sizes, Giljohann et al previously observed a positive correlation between DNA loading density and intracellular delivery of Au‐cored SNAs to three cell types, including C166 endothelial cells, HeLa cells, and A549 lung cancer cells . Zhang et al arrived at a similar conclusion by preparing two sets of polymer‐cored SNAs with sizes of ≈40 nm, 1) micellar‐SNAs coated with DNA‐brush block copolymer (DBBC) strands (302 DNA strands per particle) and 2) micellar‐SNAs coated with linear block copolymer (LDBC) strands (190 DNA strands per particle) . The authors observed that DBCC–SNAs enter HeLa cells twice as much as LDBC–SNAs.…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 91%
“…For example, common block copolymer polymer vehicles such as poly(ethylene glycol)‐ block –poly(lactic‐ co ‐glycolic acid) (PEG–PLGA) used for targeted drug delivery have shown poor loading capacity for nucleic acids. While in recent years, Mirkin and co‐workers have pioneered the use of spherical nucleic acids for gene uptake and cells and regulation, many of these studies have primarily focused on building nucleic acid micellar or liposomal structures . To expand the materials set for co‐encapsulating nucleic acids and hydrophobic drugs within a single carrier, we report here the design and implementation of synthetic DNA analogs—namely click nucleic acids (CNAs)—for synthesizing PLGA‐based polymer nanoparticles that sequester high loadings of DNA.…”
mentioning
confidence: 99%
“…The PEG was chosen in order to avoid the nonspecific adsorption of proteins at the particle surface and minimize the risk of masking the targeting FA moieties – in addition to its spacer function. In comparison to the polyester–DNA conjugates described above where additional PEG was applied only for the linear diblock copolymer (and not required for the more effective brush diblock copolymer), PEG has obviously a much larger effect if – as here – small molecules are attached to the polyester. Covalent conjugation was then successfully proven, for example, using GPC.…”
Section: Polyester Conjugation To Small Bioactive Moleculesmentioning
confidence: 99%
“…Synthesis: (A) polyester–peptide conjugates via azide click chemistry on alkyne‐grafted polyesters; (B) cRGD‐functionalized micelles via thiol click chemistry; (C) DNA block copolymers via click chemistry on PCL as graft (DBBC–SNA; top) and linear (LDBC–SNA; bottom) architectures …”
Section: Conjugates Of Biological Polymers (Nucleic Acids Peptides Amentioning
confidence: 99%
See 1 more Smart Citation